An international multicentre prospective audit of elective rectal cancer surgery; operative approach versus outcome, including transanal total mesorectal excision (TaTME). (25th September 2018) - ,
Abstract: Introduction: Transanal total mesorectal excision (TaTME) has rapidly emerged as a novel approach for rectal cancer surgery. Safety profiles are still emerging and more comparative data is urgently needed. This study aimed to compare indications and short‐term outcomes of TaTME, open, laparoscopic, and robotic TME internationally. Methods: A pre‐planned analysis of the European Society of Coloproctology (ESCP) 2017 audit was performed. Patients undergoing elective total mesorectal excision (TME) for malignancy between 1 January 2017 and 15 March 2017 by any operative approach were included. The primary outcome measure was anastomotic leak. Results: Of 2579 included patients, 76.2% (1966/2579) underwent TME with restorative anastomosis of which 19.9% (312/1966) had a minimally invasive approach (laparoscopic or robotic) which included a transanal component (TaTME). Overall, 9.0% (175/1951, 15 missing outcome data) of patients suffered an anastomotic leak. On univariate analysis both laparoscopic TaTME (OR 1.61, 1.02–2.48, P  = 0.04) and robotic TaTME (OR 3.05, 1.10–7.34, P  = 0.02) were associated with a higher risk of anastomotic leak than non‐transanal laparoscopic TME. However this association was lost in the mixed‐effects model controlling for patient and disease factors (OR 1.23, 0.77–1.97, P  = 0.39 and OR 2.11, 0.79–5.62, P  = 0.14 respectively), whilst low rectal anastomosis (OR 2.72, 1.55–4.77, P  < 0.001) and male gender (OR 2.29, 1.52–3.44, P  < 0.001) remained strongly associated. The overall positive circumferential margin resection rate was 4.0%, which varied between operative approaches: laparoscopic 3.2%, transanal 3.8%, open 4.7%, robotic 1%. Conclusion: This contemporaneous international snapshot shows that uptake of the TaTME approach is widespread and is associated with surgically and pathologically acceptable results.